Ultrathin cellulose nanofiber assisted ambient-pressure-dried, ultralight, mechanically robust, multifunctional mxene aerogels - Wu, Na (2023)
Ambient-pressure-dried (APD) preparation of transition metal carbide/nitrides (MXene) aerogels is highly desirable yet remains highly challenging. Here, ultrathin, high-strength-to-weight-ratio, renewable cellulose nanofibers (CNFs) are efficiently utilized to assist in the APD preparation of ultralight yet robust, highly conductive, large-area MXene-based aerogels via a facile, energy-efficient, eco-friendly, and scalable freezing-exchanging-drying approach. The strong interactions of large-aspect-ratio CNF and MXene as well as the biomimetic nacre-like microstructure induce high mechanical strength and stability to avoid the structure collapse of aerogels in the APD process. Abundant functional groups of CNFs facilitate the chemical crosslinking of MXene-based aerogels, significantly improving the hydrophobicity, water resistance, and even oxidation stability. The ultrathin, 1D nature of the CNF renders the minimal MXenes' interlayered gaps and numerous heterogeneous interfaces, yielding the excellent conductivity and electromagnetic interference (EMI) shielding performance of aerogels. The synergies of the MXene, CNF, and abundant pores efficiently improve the EMI shielding performance, photothermal conversion, and absorption of viscous crude oil. This work shows great promises of the APD, multifunctional MXene-based aerogels in electromagnetic protection or compatibility, thermal therapy, and oil-water separation applications.